The Service Learning: Constructing the Financial Future of YBM Briliant Scholarship Recipients through Understanding the Role and Strategies of Stock Investments - Sentosa, Dewi Suryani; Hermawan, Dimas; sartiyah, Sartiyah (Universitas Syiah Kuala, 2024)
The YBM Briliant scholarship program, administered by the national zakat institution Yayasan Baitul Maal BRIliaN, plays a crucial role in shaping competent and socially responsible human resources. However, scholarship recipients, primarily from Syiah Kuala University and Ar-Raniry State Islamic University in Aceh, face a notable gap in financial literacy, particularly concerning stock investment. Despite residing in disciplined dormitories and participating in YBM Brilian training, these students lack exposure to essential financial management skills related to stock investments. This community service initiative aims to bridge the financial literacy gap by providing YBM Briliant Aceh scholarship recipients with insights into stock investment principles and leveraging technology for improved investment performance. The objective is to empower scholarship recipients with the necessary skills for effective financial management, fostering confidence and competence in navigating the complexities of stock markets. Implemented using the Service Learning method, the project includes sessions on the Basics of Stock Investment, Technical Analysis, Stock Price Valuation, and the Use of Technology in Improving Stock Investment Performance. Initial results indicate an increased understanding of financial management through stock investment among scholarship recipients. By engaging in practical learning experiences and community service, the participants develop the knowledge and confidence required for astute financial decision-making. This community service initiative underscores the significance of disseminating knowledge on stock investment and leveraging technology to guide scholarship recipients towards informed financial management. The results highlight the positive impact of practical learning methods in enhancing financial literacy and empowering students with the skills necessary for effective stock investment. Overall, this initiative contributes to the construction of a resilient financial future for YBM Brilian Aceh scholarship recipients.